A Survey Study on Role of Oils in Context of Longevity - Pathan, Ikbal Mohammad; Meena, Anita; Gurjar, Hemwati; Dixit, Mahesh (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda, a science of life emphasizes on the maintenance, promotion of health and curing of diseases through Dincharya, Ritucharya and Aahar as well as medicine. As per Ayurveda, Aahar is Mahoshad and edible oils form an essential part of our diet. Olis (Tail) provide Strength and rigidity of skin and also helpful to longevity. The oil plays an important role in our daily life due to constitutive property and essential part of our food. The traditional medicinal system of India mentioned oils for different uses along with part of food like; for Massage, Nasya, Basti, Kavala, Gandusha etc. This article shows a study based on a survey, conducted under Nirogi Rajasthan Programme. This study was done on 1500 people aged above 60 years irrespective of their gender. The Persons were 1022 out of 1500 irrespective of their gender, use non-refined oil on a daily basis. Among these 537 were male and 485 were females. In this Study, we found that people who take non-refined oil on a daily basis have better life expectancy or Longevity. Oils are an important part of our diet either, increase or decrease in its amount leads to many systemic disorders. Alopecia, thrombocytopenia, intellectual disability, Vitamin deficiency disorders caused by Vitamin A, D, E and K are caused by lack of essential fatty acids. However fatty liver, obesity, dyslipidemia, CVD, Hypertension all are caused by excessive amounts of fat in the body. The proper amount of oil consumption and proper metabolism are essential for maintaining health. Good health deals with longevity. radical.oil or medicated oil, that can’t be move (Sneh Gandusha) The traditional medicinal system of India mentioned oils (Tail) for different uses like; for massage, Nasal oleation therapy (Nasya), Anima of oil or medicated oil (Anuvasan Basti), Rinse or Gargle of oil or medicated oil (Sneh Kavala), filling full of the mouth with so much quantity of etc. The ancient text of Ayurveda suggested that oil represents properties of its origin. As per Ayurveda oils possess Madhur ras, Kashaya anuras, Sukshma, Vyavayi, Pittakar, Malamutra vibhandkar, Ushana, Medha and Agnideepak properties and help to maintain kapha and balya along with skin rigidity(1). As per description of acharya charaka and sushrut oils offers beneficial effects